2010
DOI: 10.1021/ma100027b
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Segregation in Polymer/Fullerene Blend Films for Photovoltaic Devices

Abstract: It has recently been shown that surface energy effects can cause selective segregation at the active layer interfaces of a bulk heterojunction (BHJ) organic photovoltaic device. The active layer interface composition has been suggested to impact device performance. In this study changes in the BHJ vertical composition profile of BHJ active layers cast on two hole transport layers (HTL) with significantly different surface energies (γ) are characterized using spectroscopic ellipsometry and near-edge X-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
228
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(262 citation statements)
references
References 40 publications
32
228
1
1
Order By: Relevance
“…Another explanation is based on the link between enrichment and substrate surface energy. In ref 46, it has been shown that by consistently changing the material of the substrate into one with lower surface energy, the enrichment of PCBM also systematically decreased. The affinity of P3HT/PCBM with various cathode materials is an important question worth exploring, which we plan to investigate in the future using this framework.…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation is based on the link between enrichment and substrate surface energy. In ref 46, it has been shown that by consistently changing the material of the substrate into one with lower surface energy, the enrichment of PCBM also systematically decreased. The affinity of P3HT/PCBM with various cathode materials is an important question worth exploring, which we plan to investigate in the future using this framework.…”
Section: Resultsmentioning
confidence: 99%
“…The DSIMS results have, also, been supported by variable-angle spectroscopy ellipsometry (VASE), X-ray photoelectron spectroscopy (XPS), near-edge Xray absorption fine structure spectroscopy (NEXAFS) and neutron reflectivity (NR) studies in our laboratories and elsewhere. 42,[47][48][49][50][51] It should also be noted that the distribution of components normal to the film surface is also dependent on the nature of the solvent used. 52 The interactions between the conjugated polymer, here P3HT, and PCBM, that is, their miscibility, and the solubility of the components in the solvent use for film preparation are important parameters that must be considered in describing and controlling the morphology of the resultant active layer.…”
Section: Thermal Annealing Approachmentioning
confidence: 99%
“…This has been shown to be critical in understanding how some devices operate, as for example in section 4.2, where charge transport in the vicinity of the donor-acceptor heterojunction of an OPV had a more substantial effect on GR than did the meso-scale morphology. However, some features on the meso-scale are of interest, such as the presence of wetting layers [443] which accumulate at the electrodes OPVs [444][445][446][447][448], or the degree of mixing of the matrix and dye in an OLED [449]. Furthermore, although research has generally centred on what optical and electronic properties using a blend of OSCs can endow a device (e.g.…”
Section: Different Ways Of Defining Morphologymentioning
confidence: 99%